2016
DOI: 10.2754/avb201685030285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feed supplementation with various zinc sources on mineral concentration and selected antioxidant indices in tissues and plasma of broiler chickens

Abstract: The aim of this study was to compare the effects of organic dietary zinc (Zn) sources and zinc sulphate on mineral deposition, activity of total superoxide dismutase (SOD) and copper/ zinc SOD in tissues of broiler chickens. The performance indicators and lipid peroxidation by measuring the contents of thiobarbituric acid reactive substances (TBARS) in tissues and plasma were also evaluated. Broilers were assigned to 4 treatment groups, each replicated × 6, with 9 birds per replicate. The control group was fed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 23 publications
0
6
0
2
Order By: Relevance
“…On the other hand, the current results do not agree with several other findings where low-level supplementation with Zn from organic sources increases serum Zn, P or Ca concentration [ 14 , 17 , 19 , 41 – 43 , 61 , 66 ]. There are also recent studies showing no effect of dietary Zn on plasma Zn and Cu concentration [ 44 , 48 , 67 ]. However, in the present study, Zn, Fe and Ca concentrations increased after phytase inclusion when compared to both control groups, irrespective of Zn supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the current results do not agree with several other findings where low-level supplementation with Zn from organic sources increases serum Zn, P or Ca concentration [ 14 , 17 , 19 , 41 – 43 , 61 , 66 ]. There are also recent studies showing no effect of dietary Zn on plasma Zn and Cu concentration [ 44 , 48 , 67 ]. However, in the present study, Zn, Fe and Ca concentrations increased after phytase inclusion when compared to both control groups, irrespective of Zn supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Mwangi et al [43] specified that increasing dietary Zn and Mn supplementation were desired for a higher mineral storage in the liver. Ivanišinová, et al [44] reported that higher bioavailability of organic Zn associated with its higher concentration in the hepatic tissues. It was described that zinc influenced the absorption and biodistribution of Cu, Fe and Mn trace minerals [45].…”
Section: Mineral Contents Of Selected Tissuesmentioning
confidence: 99%
“…Recent data have indicated that inclusion of organic Zn sources in rabbit diets could improve growth performance and duodenum morphology, as well as reducing the incidence of diarrhoea in growing rabbits (Yan et al, 2017). However, some studies have shown no differences in the bioavailability of Zn between organic and inorganic sources (Ivanišinová et al, 2016). Our previous work demonstrated that dietary supplementation with 100 mg Zn/kg from inorganic or organic sources resulted in a significant increase in digestibility coefficients of Zn, Fe and Mn compared to unsupplemented rabbits and did not influence selected biochemical parameters in caecal fermentation (Chrastinová et al, 2016).…”
Section: Introductionmentioning
confidence: 99%